CONSTRUCTION MANAGEMENT ASPECTS PLANNING OF GREAT MOSQUE OF SURAKARTA - Edwin Pambudi, Vincentius
Surakarta is one of Indonesia’s big cities with relatively high of population density, comapred to other cities in West Java with most of the population is moslem. This Final Project reviewed the construction management aspects of Great Mosque of Surakarta as one of the solutions for this condition. The scope of this Final Project generally involves the creation of Work Breakdown Structures, planning of construction methods which include site plan and zoning, work volume calculations, scheduling based on productivity, and detailed cost estimation for preparatory work, ground work, lower structure work, upper structure work and water resource management work. The determination of duration of work is done based on two factors that are based on the heavy equipment leads and the labor resources leads. Detailed cost estimation were made using two methods: unit price using SNI and Permen PU no. 28 2016 and resource enumeration. This project is scheduled to be constructed for a total duration of 426 days or 1 year and 2 months. The project cost budget plan is Rp 96.975.063.723,52 with a percentage of cost for the preparatory work of 1,35%, ground work 2,786%, lower structure work 17,252%, structural work 53,084% and water resource management 0,0697%.